A Cost-benefit Analysis of the Jones Act: Petroleum Product Tankers. (1st January 2021) - Hernández, Igor; Medlock, Kenneth; Mikulska, Anna; Temzelides, Ted
The Jones Act requires that all ships connecting US ports carry the US flag, are constructed in the USA, and are owned and crewed by US citizens and permanent residents. We study the welfare effects of the Jones Act in the market of product tankers. We use supply-demand estimates to compute consumer, producer, and total surplus in the presence, and in the hypothetical absence of the Jones Act. We find that the economic welfare costs of the Jones Act in this segment amount to 751.9 million per year.